In vivo quantification of mouse autoimmune arthritis by PET/CT. (26th June 2014) - Kundu‐Raychaudhuri, Smriti; Mitra, Anupam; Datta‐Mitra, Ananya; Chaudhari, Abhijit J.; Raychaudhuri, Siba P.
Abstract: Aim: To quantify the progression and severity of mouse collagen‐induced arthritis (CIA) using an in vivo imaging tool, 18 F‐fluorodeoxyglucose ( 18 F‐FDG) PET/CT and validate it against gold standard 'histopathological' evaluation. Method: The PET radiotracer 18 F‐FDG, a marker for glucose metabolism, was injected in mice at different stages of CIA and the radiotracer distribution was imaged using a PET scanner. A sequential CT scan provided correlated anatomy. Radiotracer concentration was derived from PET/CT images for individual limb joints and on a per‐limb basis at different stages of the disease. The imaging outcomes were subjected to correlation analysis with concurrently measured clinical and histological score. Results: Clinical and histological score, and hence disease severity, showed a strong linear correlation ( r 2 = 0.71, P = 0.001 and r 2 = 0.87, P < 0.001, respectively) with radiotracer concentration measured from PET/CT during the progression of CIA. Conclusions: The strong positive correlation of the 18 F‐FDG PET/CT findings with the histopathological evaluation at different stages of the disease suggest the potential of this imaging tool for the non‐invasive assessment of progression and severity in mouse autoimmune arthritis. Thus, in preclinical studies, 18 F‐FDG PET/CT can be considered as a non‐invasive tool to develop novel therapies of inflammatory arthritis.